Hubungan Antara Kontrol Diri dan Pembelian Impulsif Merchandise K-Pop pada Penggemar K-Pop di Fase Emerging Adulhoodasa Penggemar K-Pop - Hanna Aqeela Humayra; Ditta Febrieta; Lenny Utama Afriyenti (Journal of Psychology and Social Sciences, 2026)
The Korean Wave phenomenon has increased the purchasing of K-Pop merchandise, particularly among emerging adults, which may encourage impulsive buying behavior. This study aimed to examine the relationship between self-control and impulsive buying in purchasing K-Pop merchandise among emerging adult K-Pop fans. This study employed a quantitative approach with a cross-sectional design. Participants consisted of 139 K-Pop fans aged 18–25 years who were recruited through purposive sampling from a K-Pop fan WhatsApp community in Indonesia. All participants had previously purchased K-Pop merchandise. Self-control was measured using the Brief Self-Control Scale (BSCS) developed by Tangney et al. (2004) (Cronbach's α = 0.787), while impulsive buying was measured using a scale based on the dimensions proposed by Verplanken and Herabadi (2001) (Cronbach's α = 0.899). Because the data did not meet the normality assumption, Spearman's rank correlation was used as the primary analysis with JASP software. The mean self-control score was 43.72 (SD = 6.91), while the mean impulsive buying score was 43.01 (SD = 11.17). The results showed a very weak positive and non-significant relationship between self-control and impulsive buying (ρ = 0.062, p = 0.471). These findings indicate that self-control was not significantly associated with impulsive buying of K-Pop merchandise among emerging adult K-Pop fans in this study, suggesting that other factors may play a greater role in explaining impulsive buying behavior.